“Remote sensing based Information and Insurance for Crops in emerging economies” (RIICE) in Kenya - Mathieu, Renaud; Satapathy, Sushree; Raviz, Jeny; Wafula, Kelvin; Koskei, Vincent; Mwende, Faith; Aleri, David; Cattaneo, Alessandro; Gatti, Luca; Holecz, Francesco (CGIAR Initiative on Digital Innovation, 2024)
The CGIAR Research Initiative on Digital Innovation and Transformation (WP4) seeks to improve real time monitoring of food system dynamics to inform multiple stakeholders who make time critical decisions to respond to variation and shocks, improve the flow of information for a better understanding of the food systems, and enhance digital data streams for improving decision making by food system actors. To this end, the International Rice Research Institute (IRRI) in partnership with sarmap, Switzerland, the National Irrigation Authority, and the Rice Promotion Program (Ministry of Agriculture), Kenya, is piloting a digital rice production monitoring platform. The platform RIICE (www.riice.org) is a remote sensing-based digital platform that delivers near real time, geolocalized, accurate, and updated seasonal information on rice area, yield, planting dates, and climate-driven yield losses. Initially, the rice production was monitored for the short rain season of 2023 in the Mwea irrigation scheme and will be extended to the off season in 2024, as well as to the other main rice irrigation schemes in the country. A Stakeholders Engagement meeting was organized in Nairobi for presenting and discussing the customization of the RIICE platform for Kenya. This report covers activities conducted and outputs generated for 2023 short rain season.